1998
DOI: 10.1002/(sici)1096-9063(199801)52:1<58::aid-ps632>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methyl iodide as a soil fumigant in container and small field plot studies

Abstract: Methyl iodide was evaluated as a soil fumigant as a potential replacement for the widely used soil fumigant methyl bromide. In container trials, methyl iodide was signiÐcantly more e †ective than methyl bromide against the plant parasitic nematodes Meloidogyne incognita, Heterodera schachtii and T ylenchulus semipenetrans and the plant pathogenic fungus Rhizoctonia solani. In small Ðeld plots, soil populations of root-knot nematodes were no longer detected after methyl iodide fumigation at an application rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…The quarantine treatment for pest or some other microbial control is required to protect domestic plants and animals (Kwon, Huh, Kwon, & Byun, 1999). Although fumigation (Becker, Ohr, Grech, McGiffen, & Sims, 1998), cold storage treatment (Gould & Sharp, 1990), controlled atmospheric treatment (Delate, Brecht, & Coffelt, 1990), and heat treatment (Couey, 1989) have been used selectively for quarantine methods, they have some defects such as lack of efficiency, quality deterioration, cost, and treatment time. Moreover, fumigation with methyl bromide will be prohibited as it was announced to be an environmentally disruptive substance (UNEP, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…The quarantine treatment for pest or some other microbial control is required to protect domestic plants and animals (Kwon, Huh, Kwon, & Byun, 1999). Although fumigation (Becker, Ohr, Grech, McGiffen, & Sims, 1998), cold storage treatment (Gould & Sharp, 1990), controlled atmospheric treatment (Delate, Brecht, & Coffelt, 1990), and heat treatment (Couey, 1989) have been used selectively for quarantine methods, they have some defects such as lack of efficiency, quality deterioration, cost, and treatment time. Moreover, fumigation with methyl bromide will be prohibited as it was announced to be an environmentally disruptive substance (UNEP, 1995).…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, based on its pest control efficacy, it has been suggested that it may constitute a direct replacement. 5 As a preplant soil fumigant, MeI can be used alone, or in combination with chloropicrin (CP) to control plant pathogens, nematodes, insects, and weeds on crops such as strawberries, tomatoes, peppers, ornamentals, turf, trees, and vines. 6 To reduce atmospheric emissions of soil fumigants, several strategies have been proposed and shown to be successful for fumigants such as CP and 1,3-dichloropropene.…”
Section: ' Introductionmentioning
confidence: 99%
“…Eayre et al (2000) also reported that very similar reductions in population densities of the nematode Paratylenchus were observed for both MeI and MeBr fumigation. Becker et al (1998) evaluated methyl iodide as a soil fumigant in container and small field plot studies. They concluded that MeI was an excellent soil fumigant.…”
Section: Nematode Controlmentioning
confidence: 99%
“…Similarly, Ohr et al (1996) found that for controlling the plant fungi Phytophthora citricola, P. cinnamomi, P. parasitica, and Rhizoctonia solani, MeI was equal to, or better than, MeBr. Becker et al (1998) also found that the fungal species R. solani was more strongly controlled by MeI than MeBr. For fumigant rates of 88.6, 177.2, and 354.4 mmol/m 2 , these workers found R. solani survival of 92.5, 77.5, and 10.0%, respectively, for MeBr, and 27.5, 7.5, and 0%, respectively, for MeI.…”
Section: Pathogenic Microbe Controlmentioning
confidence: 99%